2021
DOI: 10.3390/ijerph18105497
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Short Emotional Management Program on Inpatients with Schizophrenia: A Pilot Study

Abstract: The prevalence of schizophrenia is gradually increasing worldwide. Many patients with schizophrenia have a diminished ability to empathize and to detect their own emotions or those of others, deteriorating their social functioning and their quality of life. Nonetheless, emotional management training may improve patients’ emotion recognition, emotional expression, and negative symptoms. Developing and applying a short but effective program that reflects the current medical environment, in which hospital stays a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 38 publications
(48 reference statements)
1
0
0
Order By: Relevance
“…This might be linked to the need of patients with schizophrenia for help to improve their social cognition skills, emotion regulation skills and contact with others in suitable ways. These results agreed with Park et al (32) who indicated that a gradual increase in their emotion recognition score represent in improved sensitivity to facial expressions, emotional attention, and emotional clarity and improved the emotion recognition skills regarding negative emotions. Similarly, Lam et al (33) revealed that better application of adaptive emotion regulation approaches may enhance the emotion regulation process in patients with schizophrenia, therefore, informing a new management direction to help patients deal with emotional experiences.…”
Section: Discussionsupporting
confidence: 92%
“…This might be linked to the need of patients with schizophrenia for help to improve their social cognition skills, emotion regulation skills and contact with others in suitable ways. These results agreed with Park et al (32) who indicated that a gradual increase in their emotion recognition score represent in improved sensitivity to facial expressions, emotional attention, and emotional clarity and improved the emotion recognition skills regarding negative emotions. Similarly, Lam et al (33) revealed that better application of adaptive emotion regulation approaches may enhance the emotion regulation process in patients with schizophrenia, therefore, informing a new management direction to help patients deal with emotional experiences.…”
Section: Discussionsupporting
confidence: 92%